Short Communication: A new record of Giganthias immaculatus Katayama, 1954 (Perciformes: Serranidae) from Indonesia (Biodiversitas Journal of Biological Diversity, 2016)
Peristiwady T, Makatipu PCh, Du J. 2014. A new record of Giganthias immaculatus Katayama, 1954 (Perciformes: Serranidae) from Indonesia. Biodiversitas 15: 104-107. Three specimens of Giganthias immaculatus Katayama, 1954, were collected from Bitung, North Sulawesi, in October 2009, November 2009 and June 2012. The morphological data for G. immaculatus are similar to those for G. serratospinosus White & Dharmadi, 2012; those species share the following characters: dorsal fin rays IX, 11-13, anal fin rays III, 8 and lateral line high arched. However, the former is clearly distinguishable from G. serratospinosus by pectoral-fin rays 16 or 17 (vs. 13 or 14 for G. serratospinosus); ill rakers (10) + (21-24) (vs. 10+20 or G. serratospinosus). It also differs in the following: body depth, head length, predorsal length, preanal length, upper-jaw length, interorbital width. Initially, this species was collected from Izu-Õshima, Japan. Other localities of capture for this species are: Ago Bay, Shimacho Goza, Shima City, Mie Pref., Tomari, Okinawa, Japan and Taiwan and now recorded also off Bitung, Sulawesi Island, Indonesia.